Female management & the feminist foreign policy: how does the presence of a feminist foreign policy and a female chancellor in a country relate to its cultural dimensions of femininity versus masculinity and power distance according to hofstede's approach? An analysis between Sweden, Canada, France and Mexico - Castanheira, Marina Fantuci (2024)
The thesis explores the relationship between Feminist Foreign Policy (FFP) and female leadership, focusing on the cultural aspects of femininity, masculinity, and power distance as defined by Geert Hofstede. This research examines the correlation between the presence of a feminist foreign policy and a female chancellor in a nation, and its cultural predispositions towards gender roles and power strucutres. The analysis focuses on Sweden, Canada, France and Mexico. The research utilizes a qualitative technique, utilizing case studies to analyze the intricacies of each country's approach to FFP and its leadership dynamics. The results indicate that the adoption and impact of FFP are affected by the nation's cultural inclination towards gender parity and hierarchical social structure. Sweden, as the forerunner of FFP, demonstrates a possible correlation between its feminist legislative actions and its well rooted cultural ideals of little power distance and significant femininity. Canada's FIAP (Feminist International Assistance Policy) showcases a dedication to achieving gender equality, yet it does so by emphasizing the economic benefits, reflecting a well-rounded strategy impacted by measures of moderate masculinity/femininity and power distance. The examination also encompasses France and Mexico, providing insights into the intricate interplay among leadership, policy direction, and cultural factors. The argument emphasizes the necessity of comprehending cultural settings in order to improve worldwide acceptance and influence of feminist foreign policy. This investigation makes a valuable contribution to the wide discussion on gender equality, leadership, and cultural dynamics in the field of international affairs and policy-making.